Towards a revision of the genus Periclimenes: resurrection of Ancylocaris Schenkel, 1902, and designation of three new genera (Crustacea, Decapoda, Palaemonidae) - Ďuriš, Zdeněk; Horká, Ivona (ZooKeys, 2017)
Based on recently published molecular phylogenies of Indo-West Pacific palaemonid shrimps and further morphological evidence, the systematic position of several species of the polyphyletic genus Periclimenes is revised. The generic name Ancylocaris Schenkel, 1902 is re-established for the anemone-associated Periclimenes brevicarpalis. Actinimenesgen. n., is proposed for the anemone-associated Periclimenes inornatus, Periclimenes ornatellus and Periclimenes ornatus, all of which have a subspatulate first pereiopod. Cristimenesgen. n., is designated for the echinoderm-associated species, Periclimenes commensalis, Periclimenes cristimanus, and Periclimenes zanzibaricus, all with a unique carpo-propodal articulation of the second pereiopods. Rapimenesgen. n. is established for the hydroid and antipatharian-associated Periclimenes brucei, Periclimenes granulimanus, and Periclimenes laevimanus, for which the long, slender and unequal second pereiopods and prehensile ambulatory propodi are the main synapomorphic characters.
Keywords: Periclimenes; Cristimenes; Ancylocaris; Rapimenes; symbiotic shrimps; Actinimenes